(untitled) (Global Journal of Management and Business Research, 2020)
Declining shareholders#x2019; Wealth (SHW) has been a contemporary discussion globally. Studies have shown that voodoo accounting practices by management and poor audit quality have contributed to the collapse of firms and the expectation gap in shareholders#x2019; wealth maximization. Voodoo accounting practice is the magical inflation of revenues by management to deceive the stakeholders. A dearth of voodoo accounting literature that combined the practices of big bath charges, cookie jar reserves, inventory valuations and revenue recognition timing on shareholders#x2019; wealth in Nigeria. This study therefore examines the effect of voodoo accounting on shareholders#x2019; wealth in Nigeria.